The role of mitochondria in redox signaling of muscle homeostasis - Li Li Ji; Dongwook Yeo; Chounghun Kang; Tianou Zhang (Elsevier, 2020)
In the past, contraction-induced production of reactive oxygen species (ROS) has been implicated in oxidative stress to skeletal muscle. As research advances, clear evidence has revealed a more complete role of ROS under both physiologic and pathologic conditions. Central to the role of ROS is the redox signaling pathways that control exercise-induced major physiologic and cellular responses and adaptations, such as mitochondrial biogenesis, mitophagy, mitochondrial morphologic dynamics, antioxidant defense, and inflammation. The current review focuses on how muscle contraction and immobilization may activate or inhibit redox signalings and their impact on muscle mitochondrial homeostasis and physiologic implications.